Utility of 45S5 Bioactive Glass As Bone Graft Substitute for Cavitary Defects in Pediatric Bone Tumors: A Preliminary Study. Issue 9 (9th October 2022) - Samade, Richard; Jonard, Brandon; Scharschmidt, Thomas J.
Abstract : Background: Bioactive glass has become an increasingly used treatment of cavitary bone defects in a number of orthopaedic applications. The purpose of this study was to evaluate the clinical and radiographic outcomes of bioactive glass used for benign cavitary pediatric bone tumors. A specific focus was on radiographic filling of defects and occurrence of complications by tumor class. Methods: A single institution retrospective study was performed, which entailed review of the clinical and radiographic data of 21 patients who underwent surgical curettage and grafting of benign or low-grade malignant bone tumors from 2018 to 2020. In all the cases, 45S5 bioactive glass (Fibergraft; Prosidyan, New Providence, NJ) was used to fill the bone defects. For each patient, data on demographic, preoperative diagnosis, defect size, time to mobilization, radiographic filling grade, pain, and complications were obtained. The Wilcoxon-Mann-Whitney test and Kaplan-Meier survival analysis were used for comparisons between tumor classes. Results: In the 21 patients, 11 bone tumors were latent or active (class 1) and 10 were aggressive (class 2). The mean age was 13.0±3.7 years, 6 (28.6%) were female, and the median and interquartile range for initial tumor size were 18.8 (5.8 to 50.6) cm 3 . Tumors that were class 2 had significantly more complications with bioactive glass use compared with class 1 tumors [0 vs. 1 (0 to 1), P =0.040]. The time of persistent fill grade 1 or 2 defects up to final follow-up was less in class 1 versus class 2 lesions ( P =0.048). Conclusions: Bioactive glass agents have utility for treating a broad variety of pediatric bone tumors after curettage. However, focusing these agents' use in treating latent or active subtypes of bone tumors may be ideal in minimizing complications and time to higher fill grade. Level of Evidence: Level III— Therapeutic.